Philipp Sarasin papers - Sarasin, Philipp, 1888-1968.
Patient files from Sarasin's psychoanalytic practice in Basel, Switzerland. Files include background data, correspondence, transcriptions of sessions, and testing information.
Psychoanalyst.
Collection material in German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Psychoanalysis -- Switzerland -- Basel; Psychoanalysts